2014
DOI: 10.1097/nan.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Home Infusion and Self-Administration of Nanofiltered C1 Esterase Inhibitor for Routine Prophylaxis in Patients With Hereditary Angioedema and Characterization of a Training and Support Program

Abstract: Hereditary angioedema (HAE) is a rare, chronic disease of C1 inhibitor deficiency. Study researchers evaluated the prevalence of home and self-administration of nanofiltered, human-derived C1 esterase inhibitor infusions and the implementation of a nursing training and support program. Home administration rate increased from 49.0% to 75.8%. The percentage who self-administered increased from 20.3% to 43.9%. Doses per week averaged 1.85 at home compared with 1.40 in infusion centers and physicians' offices. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
2
10
0
2
Order By: Relevance
“…One study has shown that when a comprehensive self‐administration training programme is implemented, rates of self‐administration of C1 inhibitor increased from 20.3% to 43.9% within 2 years across all patient groups. The average of five visits to be successfully trained in self‐administration in this current European analysis was similar to that observed in a study conducted in the USA …”
Section: Discussionsupporting
confidence: 86%
“…One study has shown that when a comprehensive self‐administration training programme is implemented, rates of self‐administration of C1 inhibitor increased from 20.3% to 43.9% within 2 years across all patient groups. The average of five visits to be successfully trained in self‐administration in this current European analysis was similar to that observed in a study conducted in the USA …”
Section: Discussionsupporting
confidence: 86%
“…Overall, patients and family members reacted positively to the proposal of using self-administration, with a proportion of patients switching to home therapy similar to that observed in other studies [34][35][36] . For example, a recently published Danish study that followed 80 C1-INH-HAE patients for 11 years found that by the end of 2012, forty-nine percent of the patients were practicing self-therapy for acute attacks [34] .…”
Section: Discussionsupporting
confidence: 61%
“…It is also possible that some of our patients might have benefitted from additional training and assistance at home. Notably, 2 recent studies investigating the feasibility of C1-INH concentrate self-administration found that on average patients needed 5 training sessions at home to be trained, and that the preferred form of teaching was at home by a visiting nurse in the presence of a family member or caregiver [35,37] . As recommended by current guidelines, refresher training at regular intervals may also help to further improve and maintain the acquired skills [17] .…”
Section: Discussionmentioning
confidence: 99%
“…17 A descriptive analysis of database information from the United States reported that the 75% of children younger than 12 years of age were able to receive home therapy with pdC1INH after the implementation of a home therapy training program, and one child was able to self-administer home therapy. 18 …”
Section: Rationale For Home Therapy For Pediatric Haementioning
confidence: 97%